1998
DOI: 10.1136/jnnp.64.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychotic symptoms in Alzheimer's disease

Abstract: Objectives-Many clinical and biological factors have been reported to be associated with the presence of psychosis in patients with Alzheimer's disease, although the associations were variable. The aim of this study was to clarify factors associated with the presence of psychosis in patients with Alzheimer's disease. Methods-Psychiatric functioning was studied in 228 patients with Alzheimer's disease based on the results of the behavioural pathology in Alzheimer's disease rating scale or the neuropsychiatric i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
5
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 43 publications
(42 reference statements)
8
65
5
1
Order By: Relevance
“…However, the most frequent positive association has been between e4 and psychotic symptoms. Fifteen studies (including the present one) have examined psychotic symptoms, and six (including the present one) have reported that e4 increased the risk for psychosis (Ramachandran et al, 1996;Ballard et al, 1997;Harwood et al, 1999;Weiner et al, 1999;Scarmeas et al, 2002), whereas nine have found no effect of e4 (Lehtovirta et al, 1996a;Cacabelos et al, 1997;Lopez et al, 1997;Lyketsos et al, 1997;Hirono et al, 1998Hirono et al, , 1999Levy et al, 1999;Gabryelewicz et al, 2002;Sweet et al, 2002). Among the six positive studies only two others (Weiner et al, 1999;Scarmeas et al, 2002) have considered delusions and hallucinations separately.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 68%
See 3 more Smart Citations
“…However, the most frequent positive association has been between e4 and psychotic symptoms. Fifteen studies (including the present one) have examined psychotic symptoms, and six (including the present one) have reported that e4 increased the risk for psychosis (Ramachandran et al, 1996;Ballard et al, 1997;Harwood et al, 1999;Weiner et al, 1999;Scarmeas et al, 2002), whereas nine have found no effect of e4 (Lehtovirta et al, 1996a;Cacabelos et al, 1997;Lopez et al, 1997;Lyketsos et al, 1997;Hirono et al, 1998Hirono et al, , 1999Levy et al, 1999;Gabryelewicz et al, 2002;Sweet et al, 2002). Among the six positive studies only two others (Weiner et al, 1999;Scarmeas et al, 2002) have considered delusions and hallucinations separately.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 68%
“…By contrast, Weiner et al (1999) reported marginal (P ¼ 0.05) positive associations between ApoE e4 and both delusions and hallucinations. This may reflect a statistical power issue, since delusions are more prevalent among AD patients than hallucinations (Hirono et al, 1998;Bassiony and Lyketsos, 2003), including in our present sample Note: NPI, neuropsychiatric inventory. OR (odds ratio) and 95% CI are for the effect of e4 carrier status in multiple logistic regression models, with NPI subscores as dependent variables and the following additional independent variables: age, sex, education, and MMSE.…”
Section: Comparison To Other Apoe E4 Ad Psychosis Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…70 We are unaware, however, of reports of similar pedigrees for AD þ P. A number of investigations have examined whether APOE4 might contribute to the AD þ P phenotype. While one large and two smaller studies have found an association of APOE and AD þ P, [85][86][87] most reports have found no association of APOE4 with AD þ P. 33,[88][89][90][91][92][93] Furthermore, though the major effect of APOE4 on AD phenotype is to reduce age-ofonset of AD, 94 APOE4 genotype is not associated with reduced time to onset of AD þ P. 95 Nor was association of increased risk for AD þ P with the putative AD risk gene, alpha-1-antichymotrypsin (ACT) detected. 95 Similarly, there is no evidence that any of the risk genes found to be associated with AD þ P in casecontrol studies (see above) also contribute to AD risk.…”
Section: Cosegregation Of Ad þ P and Idiopathic Psychosesmentioning
confidence: 99%